Analisis de los sistemas de juego que aplican los jugadores de la liga deportiva universitaria de Loja categoria reserva durante el campeonato 2014 - Aguirre Matailo, Henry Paul (2014)
This thesis entitled " ANALYSIS OF SYSTEMS THAT APPLY GAME PLAYERS LDU Loja BOOK DURING CLASS CHAMPIONSHIP 2014 was held with the purpose of knowing how they affect the game systems that players apply LDU Loja " booking class sports training to implement corrective action to enable stakeholders to raise awareness and raise the level of effort for the improvement of this problem . The objectives have been approved the overall objective Rate the effectiveness of the game systems that apply players LDU reserve category , was approved by the specific objectives designed to analyze gaming systems most used by players in the league Deportiva Universitaria de Loja category Reserve Diagnose performance and incidence of gaming systems at the athletic performance of the players in the Liga de Loja and determine the main advantages and disadvantages of different game systems applied by players surveys , record of observation, direct observation that the same applied to athletes and coaches from the LDU Loja: the LDU Loja for this research techniques such as I use. The investigated population was established by population are athletes training in a number of 30 players and 1 coach . Finally clear and relevant results were obtained for 17% of Athlete LDU if they know the game system that applied the coach and 83% of athletes do not know the game system applied by the coach because I do not work constantly with a system if not several , and 23% of athletes LDU announce that the methods used in the game system if adequate and 77% of athletes say that the methods used in the game system are not suitable because they do not allow us to develop the best way .